Work/care policies in European welfare states: Continuing variety or change towards a common model? - Agnes Blome (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2011)
This paper investigates work/care policies in fifteen European welfare states during the last two decades in a comparative perspective. The main question is how certain work/care arrangements are supported through public policies of different welfare states and whether this has changed over time. In particular the development of leave regulations and working time policies, the provision of childcare, child allowances and types of taxation schemes which favor the reconciliation of work and care are analyzed based on a comprehensive data collection. Although an ongoing trend towards the support of the dual-earner model is clearly visible in the data, countries still differ in the current extent of work/care reconciliation policies and the pace and timing of political reforms. Moreover, hardly any country fits an ideal type of an entirely coherent policy. Different countries prioritize certain instruments over others, irrespective of the notion they have of any specific work/care arrangement. – – Dieser Artikel analysiert vergleichend Maßnahmen zur Vereinbarkeit von Familie und Beruf in fünfzehn europäischen Wohlfahrtsstaaten. Die zentrale Frage lautet, inwiefern Vereinbarkeitsarrangements durch wohlfahrtsstaatliche Leistungen unterstützt werden und ob und wie sich diese Leistungen in den letzten zwanzig Jahren verändert haben. Basierend auf einer umfassenden Datensammlung werden die Entwicklungen in den Elternzeit-, Elterngeld- und Arbeitszeitregelungen, der öffentlichen Kinderbetreuung, des Kindergeldes sowie der Steuersysteme, die die Vereinbarkeit von Familie und Beruf fördern, untersucht. Obwohl ein länderübergreifender Trend in Richtung des Zweiverdienermodells in den Daten sichtbar wird, bestehen weiterhin Unterschiede sowohl im aktuellen Entwicklungsstand der Vereinbarkeitspolitik als auch beim Reformtempo. Auffällig ist zudem, dass das Maßnahmenbündel in nahezu keinem Land kohärent ist. Unabhängig von den selbstgesteckten Zielen geben die Länder bestimmten Politikinstrumenten Vorrang gegenüber anderen.
Keywords: 300; work; care; reconciliation; policies; gender; Europe; comparison; Familie-Beruf; Sozialstaat; Familienpolitik; Vergleich; EU-Staaten